Solving Manpower Act’s Legal Redundancy Through Job Creation Act’s Foreign Manpower Utilization Plan - Pakpahan, Novritsar Hasintongan (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2021)
This research discusses the impact of Job Creation Act towards foreign workers in Indonesia. Act 11 of 2020 titled Job Creation Act has been legislated and enacted on November 2nd 2020. It also regulated manpower in Indonesia, including foreign workers in Indonesia. In the latest regulation, foreign workers are now only required to get their foreign manpower utilization plan approved. Unlike Act 13 of 2003 regarding Manpower Act, foreign employers are not required to gain foreign worker permit for their foreign worker. This research is conducted as normative research using statute and conceptual approach. The result showed that Job Creation Act had managed to solve legal redundancy between foreign worker permit and foreign manpower utilization plan. Job Creation Act stresses Presidential Act 20 of 2018 regarding Foreign Worker Utilization that foreign manpower utilization plan also act as foreign worker permit. To conclude, the regulation of foreign worker utilization in Job Creation Act had managed to solve legal redundancy in Manpower Act and support Indonesian Democratic Economy